2018
DOI: 10.1159/000478655
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an Integrative Oncological Concept in the Daily Care of a German Certified Breast Cancer Center

Abstract: Background: In recent decades the concept of integrative medicine has attracted growing interest in patients and professionals. At the Gemeinschaftskrankenhaus Havelhöhe (GKH), a hospital specialized in anthroposophical medicine, a breast cancer center (BCC) has been successfully certified for more than 5 years. The objective of the present study was to analyze how integrative strategies were implemented in the daily care of primary breast cancer patients. Methods: Clinical, demographic, and follow-up data as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 33 publications
1
22
0
6
Order By: Relevance
“…We conducted a prospective observational study for primary stage I-III breast cancer patients as reported previously [ 30 , 31 ]. Patients who gave written consent to be registered in the Network Oncology (NO) registry [ 32 ], who were diagnosed between June 2012 and April 2017 at the certified Breast Cancer Centre (Gemeinschaftskrankenhaus Havelhöhe, Berlin, Germany), and who received a tumor board advice for CTX were included.…”
Section: Methodsmentioning
confidence: 99%
“…We conducted a prospective observational study for primary stage I-III breast cancer patients as reported previously [ 30 , 31 ]. Patients who gave written consent to be registered in the Network Oncology (NO) registry [ 32 ], who were diagnosed between June 2012 and April 2017 at the certified Breast Cancer Centre (Gemeinschaftskrankenhaus Havelhöhe, Berlin, Germany), and who received a tumor board advice for CTX were included.…”
Section: Methodsmentioning
confidence: 99%
“…Facing the diagnosis of cancer can lead into an existential crisis, with feelings of loss of reality, meaning, and security, accompanied by existential fear and despair [9]. In the certified breast cancer center (BCC) of the Gemeinschaftskrankenhaus Havelhöhe [10] specialized in Anthroposophic-integrative oncology, ECLR is applied apart from regular or daily ward rounds and outside of patient rooms, by consciously giving time and space in extra interview appointments. Medical-related questions, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As indicated by a meta-analysis in 2008, the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire-C30 (EORTC QLQ-C30) was 1 of the 4 most common and well-developed valid instruments to measure HRQL in breast cancer patients. To supply high quality standards and to make the results comparable [20], data from EORTC QLQ-C30 questionnaires that were answered by patients being treated in a certified German BCC were evaluated in the present study; the BCC is annually audited by the country's largest scientific-oncological medical expert association, the German Cancer Association (DKG) [10]. …”
Section: Introductionmentioning
confidence: 99%
“…This finding seems to contradict other studies that reported the largest number of CM provisions in oncology departments. 4,[20][21][22][23][24][25][26][27] The main motivations to provide and maintain CM in this project were symptoms such as pain, anxiety, or insomnia; difficult care situations; and positive feedback from patients and health care professionals. In other settings, reasons to deliver CM included pain, anxiety, 4,28 prevention of drugrelated side effects, 4,28 scientific evidence for some CMs, 4,29 management of chronic diseases, 2,28 patient or employee requests, 4,7,28 long hospitalizations, 28 or patients not responding to conventional medicine.…”
Section: Assessment Of Current Practicementioning
confidence: 99%